The study of dry biological valve crosslinked with a combination of carbodiimide and polyphenol. Issue 1 (3rd December 2020) - Yang, Li; Xie, Shuang; Ding, Kailei; Lei, Yang; Wang, Yunbing
Abstract: The glutaraldehyde crosslinked pericardium has been used in bioprosthetic valves for about 50 years. However, problems such as glutaraldehyde residue and calcification still exist in current commercial products. Non-glutaraldehyde crosslinked dry valve is an important strategy to solve those problems. In this study, a non-glutaraldehyde crosslinked dry biological valve material was obtained by the combined crosslinking of carbodiimide (EDC) and polyphenol. The results showed that the comprehensive properties of EDC and curcumin crosslinked pericardium were superior to glutaraldehyde crosslinked pericardium, including unfolding property, anti-calcification, cytotoxicity, anticoagulant properties, mechanical properties, enzyme degradation resistance and thermal shrinkage temperature. EDC and curcumin crosslinked dry pericardium could flatten after being folded at 40°C for 3 days while glutaraldehyde crosslinked pericardium could not. The calcification of pericardium treated with EDC and curcumin was 1.21 ± 0.36 mg/g in rats after 60 days' subdermal implantation, much lower than that of glutaraldehyde treated control group (22.06 ± 3.17 mg/g).